PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR STATISTIKA MAHASISWA PADA FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAIN PALU - Karmawati Karmawati (ISTIQRA, 2015)
This study aimed to: determine student learning outcomes by applying statistical learning methods of problem solving in the Faculty of Teacher Training and Education IAIN Palu; also to know the motivation of the students towards subjects studied statistics at the Faculty of Teacher Training and Education IAIN Palu. This research is a class action (classroom action research). The study population was all students of Faculty of Teacher Training and Education IAIN Palu with a total sample of 49 people. Sample selection is done by using purposive sampling technique followed by simple random sampling technique. Data collection is done by using the test, questioner and observation. Data analysis was performed by calculating the average of the results of tests each cycle to determine the increase in student results and questionnaires and observation to determine the improvement of student learning motivation. The results showed that: (1) the results of a statistical study increased after learning method applied problem solving in students of Teacher Training Faculty of Teacher Training and Education IAIN Palu namely, from 66.14 increased to 79.54; (2) learning motivation of students to courses at the Faculty of Teacher Training and Education IAIN Palu increased namely increasing student attendance (96.27% to 98.31%), increasing the number of students who complete the task (94.22% to 97, 23%), the increase of students who completed the problem on the board (2.71% to 5.10%), the increase of students who asked questions during the learning takes place (4.08% to 6.47%), and decreased student late (3.41% to 1.70%). The number of students who love to learn the statistics that 39 people; students are happy with the given problem/statistical problems to be resolved by 41 people. However found in this study was less interested students to conduct quantitative research that is only 5 people